1992
DOI: 10.1104/pp.99.4.1590
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cytosolic mRNAs Between Polysomal and Ribonucleoprotein Complex Fractions in Alfalfa Embryos

Abstract: Cell-free translational and northern blot analyses were used to examine the distribution of storage protein messages in the cytoplasmic polysomal and mRNA-protein complex (mRNP) fractions during development of somatic and zygotic embryos of alfalfa . No special array of messages was identified in the mRNP fraction; however, some messages were selectively enriched in either the polysome or mRNP fractions, and their distribution pattern varied quantitatively during development of the embryos. During the earliest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The characterization of the stored mRNA has remained elusive for a long time, and just recently some of these mRNAs have been identified [1,22]. In the present research we identified RPs among the early products of c~-amanitin-treated germinating axes, which proved the presence of RP-mRNAs within the population of stored mRNAs.…”
Section: Discussionsupporting
confidence: 53%
“…The characterization of the stored mRNA has remained elusive for a long time, and just recently some of these mRNAs have been identified [1,22]. In the present research we identified RPs among the early products of c~-amanitin-treated germinating axes, which proved the presence of RP-mRNAs within the population of stored mRNAs.…”
Section: Discussionsupporting
confidence: 53%
“…Stored mRNAs appear to support embryo development until the eight-cell stage in the fern Marsilea vestita (Kuligowski et al, 1991), and maternal mRNAs are activated in early zygote development in Fucus (Masters et al, 1992). In addition, Pramanik et al (1992) demonstrated that storage protein synthesis in alfalfa somatic embryos is translationally regulated; the mRNA is present but restricted to the nontranslated mRNP pool early in embryogenesis (globular-tetorpedo stages) and is then shifted to the polysome pool at the cotyledon stage. Moreover, posttranscriptional regulation, including differential transcript stability, has been suggested to be an important component of embryo mRNA accumulation in zygotic embryos (Walling et al, 1986).…”
Section: Other Genes Lsolated From Somatic Embryosmentioning
confidence: 99%
“…Development of somatic embryogenesis has been described to follow patterns similar to the ones of zygotic embryogenesis (Konar et ai., 1972;Altamura et ai., 1992); however, in studies conducted on model plants, it proved to be more variable in early division patterns (McWilliam et ai., 1974;Dos Santos, 1983) and further morphological development (Toonen et ai., 1994;Mordhorst et al, 1997), cellular organell composition (Taylor and Vasil, 1996), and gene expression as well (Pramanik and Krochko, 1992; In model plants, somatic embryogenesis is the most utilized model system for plant cell totipotency and developmental studies, while it is one of the most powerful techniques offered by tissue culture for genetic improvement of species important to agriculture.…”
Section: Introductionmentioning
confidence: 99%